The role of IL-12, IL-23 and IFN-γ in immunity to viruses - Novelli, Francesco (Cytokine Growth Factor Rev, 2004)
IL-12, IL-23 and IFN-γ form a loop and have been thought to play a crucial role against infectious viruses, which are the prototype of “intracellular” pathogens. In the last 10 years, the generation of knock-out (KO) mice for genes that control IL-12/IL-23-dependent IFN-γ-dependent mediated immunity (STAT1, IFN-γR1, IFNγR2, IL-12p40 and IL-12Rβ1) and the identification of patients with spontaneous germline mutations in these genes has led to a re-examination of the role of these cytokines in anti-viral immunity. We here review viral infections in mice and humans with genetic defects in the IL-12/IL-23-IFN-γ axis. A comparison of the phenotypes observed in KO mice and deficient patients suggests that the human IL-12/IL-23-IFN-γ axis plays a redundant role in immunity to most viruses, whereas its mouse counterparts play a more important role against several viruses.